PENGARUH BEBAN KERJA,STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA TENAGA MEDIS PUSKESMAS SEMUDUN KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH - Admin, Ramlah B1021151021 (Jurnal Manajemen Update, 2020)
This study aims to test and analyze the influence of Workload, Work Stress and Work Environment on the Performance of Semudun Health Center Medical Staff in Sungai Kunyit District, Mempawah Regency. This type of research is a causal study with a quantitative approach to examine the influence between variables, where hypothesis testing uses descriptive statistical analysis and multiple linear regression analysis. The research sample consisted of 30 medical personnel samples selected using non random sampling techniques.     The results showed the workload has a negative and significant effect on the performance of medical personnel, work stress has a positive and not significant effect on the performance of medical personnel while the work environment has a positive and significant effect on the performance of medical personnel. The female independent variable in explaining its effect on performance variable is 93.8%, while the rest is explained by other variables outside the research model.Keywords: Workload, Work Stress, Work Environment and Performance.  Daftar PustakaGibson,& Ivan, C. D. (2009). Organisasi. Jakarta: Erlangga.Lisnayetti., (2006). Beban  Kerja dan KinerjaDosenPoltekes Padang. Working Paper Series, 3. November.Mangkunegara. (2006). SumberDayaManusiaperusahaan. Bandung :RemajaRosdakarya.Manzoor., Aasia., Hadia A., &Sabita M. (2012). Investigating The Impact Of Work Stress On Job Perfomance: A Study on Textile Sector of Faisal abad.AsianJournal of Business and Management Sciences, 2 (1): pp: 2028. Munandar, A. S., (2008). PsikologiIndustri dan Organisasi. Jakarta: Universitas Indonesia (UI-Press).Sedarmayanti., (2001). ManajemenPerkantoran Modern. Bandung: MandarMajuTaiwo, A. S., (2009). The influence of work environment on workers. African Journal of Business Management, volume 4.